Ocean acidification enhances the growth rate of larger diatoms - Wu, Y; Campbell, DA; Irwin, AJ; Suggett, DJ; Finkel, ZV (2014)
Ocean acidification is changing the nature of inorganic carbon availability in the global oceans. Diatoms account for ~ 40% of all marine primary productivity and are major contributors to the export of atmospheric carbon to the deep ocean. Larger diatoms are more likely to be stimulated by future increases in CO2 availability as a result of their low surface area to volume ratio and lower diffusive flux of CO2 relative to their carbon demand for growth. Here we quantify the effect of the partial pressure of carbon dioxide ((PCO2), at levels of 190, 380, and 750 μL L-1, on the growth rate, photosystem II electron transport rate (ETR), and elemental composition for five diatom species ranging over five orders of magnitude in cell volume. Growth rates for all species were enhanced under 750 relative to 190 and 380 μL L-1, with little change in ETR or elemental stoichiometries, indicating an enhanced allocation of photochemical energy to growth under elevated PCO2. PCO2 enhancement of growth rates was size dependent. Under 750 vs. 190 μL L-1 partial pressures, growth rate was enhanced by ~ 5% for the smaller diatom species to ∼ 30% for the largest species examined. The size dependence of CO2-stimulated growth enhancement indicates that ocean acidification may selectively favor an increase in the growth rates of larger vs. smaller phytoplankton species in the sea, with potentially significant consequences for carbon biochemistry. © 2014, by the Association for the Sciences of Limnology and Oceanography, Inc.